PENGEMBANGAN ASPEK LEGAL FORMAL DAN PENGEMBANGAN USAHA KELOMPOK TANI ORGANIK - Putriana Kristanti; Purwani Retno Andalas; Agustini Dyah Respasti (Fakultas Bisnis UKDW, 2016)
This article is the result of science and technology program implementation for the community. Thisservice program aims to help solve the problems of partners, which are Organic Farmers GroupMulyo Karangdowo Sesarengan that located in the district Klaten, Central Java. The groups is noyet gained recognition from local authorities and other parties. The solve problem through informaldiscussion groups, counseling, workshops, and mentoring. Service held by the method: situationanalysis, problem identification, determining the purpose of work, problem-solving plan, socialapproach, implementation, and evaluation of activities and results. The outcome of this programare: (1) the legal aspect are the PIRT and the status of the group; (2) the formal aspects, namely theArticles of Association, the organizational structure, a list of management board, job descriptions,and standard operating procedures; (3) business aspects of organizational, marketing, and financialmanagement and financial reporting.Keywords: farmers group, formal legal aspects, articles of association, business aspects